2013
DOI: 10.1080/87565641.2012.733786
|View full text |Cite
|
Sign up to set email alerts
|

Development of Affective Theory of Mind Across Adolescence: Disentangling the Role of Executive Functions

Abstract: Theory of mind, the ability to understand mental states, involves inferences about others' cognitive (cognitive theory of mind) and emotional (affective theory of mind) mental states. The current study explored the role of executive functions in developing affective theory of mind across adolescence. Affective theory of mind and three subcomponents of executive functions (inhibition, updating, and shifting) were measured. Affective theory of mind was positively related to age, and all three executive functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 36 publications
10
71
0
1
Order By: Relevance
“…For instance, it has been found that the EF–ToM relationship extends to children between 4 1 / 2 and 6 1 / 2 years for second-order false-belief tasks and more demanding EF tasks (Perner et al, 2002). Similar results have been reported for children of middle childhood (Yang et al, 2009; Calderon et al, 2010) and in adolescents (Vetter et al, 2013). However, results in a sample of 8 1 / 2 year-olds with and without attention deficit hyperactivity disorder (ADHD) were less conclusive (Charman et al, 2001).…”
Section: Introductionsupporting
confidence: 89%
“…For instance, it has been found that the EF–ToM relationship extends to children between 4 1 / 2 and 6 1 / 2 years for second-order false-belief tasks and more demanding EF tasks (Perner et al, 2002). Similar results have been reported for children of middle childhood (Yang et al, 2009; Calderon et al, 2010) and in adolescents (Vetter et al, 2013). However, results in a sample of 8 1 / 2 year-olds with and without attention deficit hyperactivity disorder (ADHD) were less conclusive (Charman et al, 2001).…”
Section: Introductionsupporting
confidence: 89%
“…c To estimate general cognitive ability the subtests Similarities, Block Design, Vocabulary, and Matrices from the Wechsler Intelligence Scale For Children (WISC-IV, German adaptation; Petermann and Petermann, 2007) chosen IAPS pictures beyond recognition using picture manipulation software (www.gimp.org). Because the development of emotion recognition in facial stimuli (Vetter et al, 2013(Vetter et al, , 2014 might interfere with the development of emotional attention targeted here, we used emotional scenes rather than faces. One pair was arranged horizontally and the other vertically around a fixation cross (Fig.…”
Section: Stimuli Design and Proceduresmentioning
confidence: 99%
“…This prediction was also supported by several studies in childhood and adolescence that examined what can be regarded as a cognitive component of empathy, in that it refers to an emotional inference triggered by an emotional event experienced by a character. These studies showed that this ability becomes more efficient between 8 and 12 years of age (Choudhury, Blakemore, & Charman, 2006) and continues to improve between the ages of 12-13 and 19 years (Keulers et al, 2010;Van der Graaff et al, 2014;Vetter et al, 2013). By contrast, extrapolating from Davis and Franzoi's (1991) study with adolescents, we assumed that the DIS response would decline.…”
Section: The Development Of the Three Components Of Empathymentioning
confidence: 99%